2015
DOI: 10.1007/s00394-015-0871-8
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamin intake and mortality in three Central and Eastern European urban populations: the HAPIEE study

Abstract: PurposeThe aim of the study was to assess the relationships between individual-level dietary intakes of antioxidant vitamins C, E and beta-carotene with all-cause and cause-specific mortality in three Central and Eastern European (CEE) populations.MethodsData from the Health, Alcohol and Psychosocial factors in Eastern Europe cohort study were used. At the baseline survey, between 2002 and 2005, 28,945 men and women aged 45–69 years were examined in Novosibirsk (Russia), Krakow (Poland) and seven Czech towns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 45 publications
(82 reference statements)
6
44
0
Order By: Relevance
“…Vitamin C and selenium are among anti-inflammatory components of DII [23]. At the same time, there are also other studies that have shown no association between red meat, vitamin C, and selenium; and inflammation [79][80][81] and mortality [82,83].…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin C and selenium are among anti-inflammatory components of DII [23]. At the same time, there are also other studies that have shown no association between red meat, vitamin C, and selenium; and inflammation [79][80][81] and mortality [82,83].…”
Section: Discussionmentioning
confidence: 94%
“…Five additional studies1415161718 were excluded because we cannot get sufficient data to recalculate the RR or 95%CI for the highest versus lowest group. After exclusion, 13 articles (dietary intake: seven publications; circulating concentration: seven publications)5678101920212223242526 were included in this meta-analysis, of which one study21 reported results for both dietary and circulating level of beta-carotene, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies56719202122 including 11,810 deaths among 149,774 cohort members were included in the analysis, which indicated that a high intake of beta-carotene was related to a significant reduced risk of all-cause mortality (RR for highest vs. lowest group = 0.83, 95%CI: 0.78–0.88) with no evidence of between study heterogeneity ( I 2  = 1.0%, P  = 0.416) under a random-effect model (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibre, as well as other bioactive compounds found in fruits and vegetables, including flavonoids and antioxidant vitamins, may protect against the development of various non-communicable diseases. Although the cardioprotective properties of those substances still remain not fully explained, their intake has been associated with lower risk of CVD development and mortality [18][19][20][21]. Also, the consumption of fruit and vegetables itself had a beneficial effect on CVD prevention [22,23].…”
Section: Discussionmentioning
confidence: 99%